ChemInform Abstract: Copper‐Catalyzed ortho‐Acylation of Phenols with Aryl Aldehydes and Its Application in One‐Step Preparation of Xanthones. Issue 13 (18th March 2013) - Hu, Jun; Adogla, Enoch A.; Ju, Yong; Fan, Daping; Wang, Qian
Abstract A series of benzophenones (V) is obtained by ortho‐acylation of phenols with aryl aldehydes.